Neurotrauma: 2024 update - Priemer, David S.; Perl, Daniel P. (Free Neuropathology, 2024)
2023 was an important year for research in traumatic brain injury (TBI), particularly as it concerned interests in neuropathology. After reviewing the literature, we present the advancements that we felt were of particular importance to the neuropathology community. Highlighted are articles that report upon: (1) the first large-cohort assessment for the neuropathology of intimate partner violence, (2) the assessment of chronic traumatic encephalopathy (CTE) in young athletes, (3) the observation of cortical sulcal depth vascular changes in CTE, (4) a proposal for a tau immunohistochemical panel to evaluate complex cases of CTE in the context of multiple tauopathies, (5) the relationship of TBI and/or CTE with TDP-43 pathology, (6) repetitive TBI inducing pathology in C9orf72-transgenic mice, (7) radiologic patterns of head and neck injury following vehicular underbody blast exposure, (8) chronic alterations in brain metal content following repetitive impact TBI, (9) neurovascular unit injury following low-level blast exposure, and finally (10) an assessment of Muhammad Ali’s clinical history leading to the conclusion that he suffered from young-onset, idiopathic Parkinson Disease. We close our writing with in memoriam to Dr. Byron A. Kakulas, a renowned figure in the neuropathology of spinal cord injury who we lost in 2023.